Effect of Total Asset Turnover and Net Profit Margin on Company Value at PT Bumi Resources Tbk from 2012 to 2021 - Nurul Anisa (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2023)
This study aims to determine the effect of Total Asset Turnover and Net Profit Margin on Firm Value at PT. BUMI Resources, Tbk. Period 2012-2021. This type of research is quantitative. The data source used in this study is secondary data, namely the company's financial report data that has been provided by PT. BUMI Resources, Tbk. For the 2012-2021 period. The results of this study indicate that partially Total Asset Turnover has a significant effect on Firm Value while Net Profit Margin has no significant effect on Firm Value. Simultaneously Total Asset Turnover and Net Profit Margin together have no significant effect on Firm Value.